THE EFFECTS OF GRAMMAR MASTERY AND READING HABIT TOWARDS STUDENTS’ WRITING SKILL IN RECOUNT TEXT - Dewi Mustika Sari; Gustaman Saragih (Universitas Indraprasta PGRI, 2019)
This research aims to determine the effects of grammar mastery and reading habits on students’ writing skills in recount text at State Junior High School in Tangerang Regency. The population is students from state junior high schools. The 60 samples were gained through a cluster. The data was analyzed by using the multiple regression method. The results are: 1) There are any significant effects of grammar mastery and reading habits jointly towards students’ writing skills in recount text. It is proved by Sig.= 0.000 < 0.05 and Fobserved = 20.653; 2) There is a significant effect of grammar mastery towards students’ writing skills in recount text. It is proved by Sig.= 0.001 < 0.05 and tobserved = 3.435; 3) There is a significant effect of reading habit on students’ writing skills in recount text. It is proved by Sig.= 0.000 < 0.05 and tobserved = 4.639.